Petai belalang biomass as adsorbent for malachite green dye - Lee, Yen Chen (2015)
The objective of this study is to study the adsorption properties of malachite green dye using Petai Belalag biomass. Petai Belalang wood particles as a low cost and environmental friendly adsorbent has been used for removal of malachite green dye from aqueous solution. This study was carried out to investigate the effect of various experimental parameters such as contact time, temperature. pH, initial concentration of adsorbate, size of adsorbent particles and adsorbent dosage on the adsorption behavior of the biomass. Results showed that adsorption at 60 minutes with room temperature, pH value of 4, smaller particle size and high adsorbent dosage are the optimum parameters for the adsorption process to be carried out. Investigation on different equilibrium isotherms showed that the adsorption of malachite green dye on Petai Belalang fit well with Freundlich adsorption isotherm.